INVESTIGATING ELECTRICAL RESPONSE TO WATER SATURATION OF AGBADA SANDSTONE IN AN X-FIELD NIGER DELTA, NIGERIA - UGBENA, Kelvins Godfrey; NWANKWO, Cyril N.; OMALI, Aurelius O. (GeoScience Engineering, 2019)
In an attempt to characterize a reservoir in a field, importance is given to living models as it serves critical function in estimating if the reservoir under study is economically viable. Having a good knowledge of electrical response to reservoir rocks is important in characterizing and modeling the behavior of fluids at the subsurface. In this study, core plugs extracted from core barrels in a Niger Delta oil field were analyzed in the laboratory in order to determine the electrical properties of the samples and their relationship with each other and formation fluid. This was achieved by using a brine of a known concentration for simulation of core plugs. Results obtained show that for the unconsolidated sandstone, Formation resistivity factor increases with an increase in confining pressure. This characteristic depends on the porosity of the Formation and type of fluid present. Resistivity values in a reservoir will increase with an increase in capillary pressure and decrease with water saturation. The decrease in cementation exponent increases the rate of permeability in reservoir sand. However, resistivity values decrease with clay presence in reservoir sand. Keywords: Core plug, reservoir, resistivity, water saturation DOI 10.35180/gse-2019-0015